Soybean processing wastewater purification via Chlorella L166 and L38 with potential value-added ingredients production. (September 2019) - Qiu, Yiting; Zu, Yilin; Song, Chunfeng; Xie, Meilian; Qi, Yun; Kansha, Yasuki; Kitamura, Yutaka
Abstract: Microalgae have been considered as an efficient microorganism for wastewater purification with simultaneously potential value-added ingredients production. In this study, two Chlorella sp. (i.e. L166 and L38) were cultured in the soybean wastewater under three different dilution ratios (0, 10 and 100 times). The experimental results indicated that L38 cultivated in 10 times diluted soybean wastewater presented the highest total nitrogen (TN), total phosphorus (TP) and chemical oxygen demand (COD) removal efficiency (i.e. 84.7%, 97.3% and 70.5%, respectively). L166 cultivated in 10 times diluted soybean wastewater showed the highest lipid (7.22 mg/L/d) and polysaccharide (2.86 mg/L/d) productivities. In addition, fatty acids methyl esters (FAME) profiles also indicated that L166 could be a promising alternative for biodiesel production with efficient soybean wastewater purification. Graphical abstract: Unlabelled Image Highlights: Two Chlorella sp . (i.e. L166 and L38) were cultured to purify soybean wastewater. Value-added byproducts yield during purification process were investigated. L38 presented efficient purification efficiency in the diluted soybean wastewater. L166 could be a promising alternative for biodiesel production.